An exploration of community-based organizations' information management challenges - Joseph, Pauline (Information Research, 2015)
Introduction: Community-based organizations are struggling to manage their current, historical and archival information assets, which impact on the information practices and seeking behaviour in these communities. This paper explores what these challenges are and proposes sustainable solutions with the help of cultural institutions. Methods: Research data were gathered from student projects, participant workshops and a case study with the motor sport community. Analysis: This study draws on the qualitative analysis of a range of sources. Results: The findings scope the information management challenges experienced generally in community-based organisations with detailed insights into the difficulties evident in the motor sport community. Conclusion: A common system to register, capture, access and preserve community-based information assets is recommended to be hosted by an Australian cultural institution in their capacity as ‘keepers’ of Australia’s history, archives and heritage.